Role of miR‐31 and SATB2 in arsenic‐induced malignant BEAS‐2B cell transformation. Issue 8 (17th April 2018) - Chen, Qiao Yi; Li, Jinquan; Sun, Hong; Wu, Feng; Zhu, Yusha; Kluz, Thomas; Jordan, Ashley; DesMarais, Thomas; Zhang, Xiaoru; Murphy, Anthony; Costa, Max
Abstract : Arsenic is a naturally occurring and highly potent metalloid known to elicit serious public health concerns. Today, approximately 200 million people around the globe are exposed to arsenic‐contaminated drinking water at levels greater than the World Health Organization's recommended limit of 10 parts per billion. As a class I human carcinogen, arsenic exposure is known to elicit various cancers, including lung, skin, liver, and kidney. Current evidence suggests that arsenic is capable of inducing both genotoxic and cytotoxic injury, as well as activating epigenetic pathways to induce carcinogenesis. Our study identifies a novel pathway that is implicated in arsenic‐induced carcinogenesis. Arsenic down‐regulated miRNA‐31 and the release of this inhibition caused overexpression of special AT‐rich sequence‐binding protein 2 (SATB2). Arsenic is known to disrupt miRNA expression, and here we report for the first time that arsenic is capable of inhibiting miR‐31 expression. As a direct downstream target of miR‐31, SATB2 is a prominent transcription factor, and nuclear matrix binding protein implicated in many types of human diseases including lung cancer. Results from this study show that arsenic induces the overexpressing SATB2 by inhibiting miR‐31 expression, which blocks the translation of SATB2 mRNA, since levels of SATB2 mRNA remain the same but protein levels decrease. Overexpression of SATB2 induces malignant transformation of human bronchial epithelial (BEAS‐2B) cells indicating the importance of the expression of miR‐31 in preventing carcinogenesis by suppressing SATB2 protein levels.